Comparisons of observed and modelled lake δ18O variability - Jones, M.D.; Cuthbert, M.O.; Leng, Melanie J.; McGowan, Suzanne; Mariethoz, G.; Arrowsmith, C.; Sloane, Hilary J.; Humphrey, K.K.; Cross, Iain (Elsevier, 2015)
With the substantial number of lake sediment δ18O records published in recent decades, a quantitative, process-based understanding of these systems can increase our understanding of past climate change. We test mass balance models of lake water δ18O variability against five years of monthly monitoring data from lakes with different hydrological characteristics, in the East-Midlands region of the UK, and the local isotope composition of precipitation. These mass balance models can explain up to 74% of the measured lake water isotope variability. We investigate the sensitivity of the model to differing calculations of evaporation amount, the amount of groundwater, and to different climatic variables. We show there is only a small range of values for groundwater exchange flux that can produce suitable lake water isotope compositions and that variations in evaporation and precipitation are both required to produce recorded isotope variability in lakes with substantial evaporative water losses. We then discuss the potential for this model to be used in a long-term, palaeo-scenario. This study demonstrates how long term monitoring of a lake system can lead to the development of robust models of lake water isotope compositions. Such systematics-based explanations allow us to move from conceptual, to more quantified reconstructions of past climates and environments.